Baleen hormone analyses reveal stress and reproductive life-history of the critically endangered Rice’s whale (Balaenoptera ricei) - Rebecca G. Evey; Matthew S. Savoca; John Ososky; Michael R. McGowen; Jeremy A. Goldbogen; Michael Cherney; Allison Case; Kathleen E. Hunt (PLoS ONE, 2026)
The Rice’s whale ( Balaenoptera ricei ) is a recently described species of baleen whale found in the Gulf of Mexico. With fewer than 50 adults remaining, the Rice’s whale is the most endangered baleen whale species. Analyses of reproductive and adrenal hormones promote the understanding of reproductive cycles and stress physiology in this rare and poorly understood species. Baleen plates contain steroid hormones stored throughout the period of baleen growth and have been used for continuous, multi-year retrospective assessment of the reproductive and glucocorticoid history of individual whales. We measured progesterone, testosterone, cortisol, and corticosterone in baleen plates of seven individual Rice’s whales (four males — one of which was the holotype — and three females), including two individuals believed to have died from starvation and one known to have been killed by ship strike. Baleen powder was obtained by drilling every 1 cm (~15–30 day intervals) from the base of the plates to the distal end. Hormones were quantified with enzyme immunoassay kits, and presence of the specific hormones was further confirmed with analytical chemistry. All assays passed validation assays for Rice’s whale baleen extract. In the two individuals that likely died of starvation, all four steroid hormones show increases in the most recently grown baleen, a pattern observed in other baleen whales in cases of prolonged illness or injury before death. A female with a known recent pregnancy had a sustained elevation of progesterone spanning the majority of her plate, indicating that baleen analysis in this species can detect recent pregnancies. No evidence of annual testosterone cycles was noted in three adult males, suggesting that this subtropical species might not have strong seasonal reproduction, which is atypical for baleen whales. Thus, we conclude that baleen hormone analysis can be used to clarify life history patterns in this critically endangered species.